Primary Stenting Immediatly after Surgery in Occluded Anastomoses of Aortoaortic Tube Graft: A Case Report. (20th July 2010) - Rabellino, M.; García-Nielsen, L.; Zander, T.; Baldi, S.; Estigarribia, A.; Zerolo, I.; Cheves, H.; Llorens, R.; Maynar, M.
Abstract : The conventional elective open procedures for abdominal aortic aneurysm repair are reliable and yield durable results. The aortoaortic tube graft has the lowest morbidity incidence when compared with different techniques. Albeit infrequent, thrombosis can be present in the first 30 days. Its treatment consists in thrombectomy and anastomosis evaluation, but with an increase in morbidity, especially in patients with urgent reintervention. This is a case report of a patient with aortoaortic tube graft, who present critical left limb ischemia immediately after surgical procedure. Angiography showed complete occlusion of left common iliac artery, affecting the distal graft anastomosis. The occlusion was resolved with endovascular treatment, and a noncovered, self-expanding, nitinol stent was deployed (primary stenting) covering the distal bypass anastomosis, with no complications and complete lower limb perfusion recovery. One month later, the patient was still asymptomatic, with distal pulse palpable and ankle-brachial index 1.